A clinical study of minimal blood flow clamping combined with 3D printing technology in laparoscopic nephron-sparing surgery - Yang, Lingbo; Wei, Pengtao; Li, Xiaohui; Sun, Jiantao (Frontiers in Oncology, 2025)
ObjectiveTo compare the safety and effectiveness of minimum flow clamping combined with 3D printing technology and highly selective renal artery clamping in laparoscopic nephron-sparing surgery.MethodsFifty-two patients with renal cancer undergoing partial resection admitted to Luoyang Central Hospital Affiliated with Zhengzhou University from 2018-01 to 2021-12 were randomly divided into two groups. Group A comprised 30 cases that underwent laparoscopic partial nephrectomy by minimal blood flow clamping combined with 3D printing technology. Group B comprised 22 cases that underwent laparoscopic partial nephrectomy by highly selective renal artery clamping technology. The operation time, renal artery branch clamping time, intraoperative blood loss, postoperative renal function injury, and complication rate were compared between the two groups.ResultsThe operation time, blood loss, renal function injury, and complication rate of Group A were shorter than those of Group B (p < 0.05). The time of renal artery clamping in Group B was shorter than that in Group A (p < 0.05). There was no statistical significance in the positive rate of resection margin between the two groups (p > 0.05).ConclusionsIn laparoscopic nephron-sparing surgery, minimum blood flow clamping technology not only can meet the requirements of accurate tumor resection but also can maximize the preservation of residual renal function, greatly shorten the operation time, reduce the amount of blood loss, and reduce the incidence of perioperative complications, making it worthy of promotion in clinical work. Clinical Trial Registration: [website], identifier [registration number].